Performance Issues Along The Six Elements of Holcim Solusi Rumah's Marketing Mix and Solution Recommedations - Susana, Apriliani Dewi; Titus, Amol (The Indonesian Journal of Business Administration, 2013)
This study aims at identifying key issues in SR franchise business along the six elements of marketing mix: people, partner, place, product, promotion, and price, and then propose solution recommendations for the identified issues. Data is collected through a method of in-depth interviews with key SR stakeholders, internally and externally, namely end customers, SR personnels, and SR franchisees. Issues identified are mapped into a Problem Tree Analysis diagram to determine causal relations among the scattered issues that lead to a general core problem and their impacts. Solutions to the mapped issues are then formulated using an Objective Tree in order for recommended actions to be given. Keywords: marketing mix, problem tree, problem tree, solution tree